The European Union and South Korea : the legal framework for strengthening trade, economic and political relations / edited by James Harrison. - Harrison, James, 1979- (Edinburgh University Press, 2013)
Every essay in this volume is written by European and Korean experts in international law. Each examines a particular aspect of the legal framework for EU-Korea relations, analysing the scope and substance of the relevant legal rules, as well as the opportunities and challenges for future cooperation. The contributions cover a wide range of policy areas, including trade, competition, and investment, as well as cooperation in non-economic areas, such as environmental protection and security policy, and aim to offer insights not only into the state of EU-Korea relations, but also potential lessons for other bilateral and regional initiatives.